Intangible Fruitions - Virtualization of Cultural Heritage for the Territorial Promotion - Francini, Mauro; Colucci, Maria; Palermo, Annunziata; Viapiana, Maria Francesca (TeMA - Journal of Land Use, Mobility and Environment, 2012)
The topic of smart cities and communities now plays an important role in the European and national policy planning, finding direct feedback in various national and international research programs, including the one under consideration. Specifically, as indicated by the Ministry of Instruction, University and Research, "a territory can be defined as "smart" when it focuses its development efforts in the human and social capital, in transport and information and communication technologies, in the careful management of natural resources and promotion of participatory governance". With this in mind we felt the need to launch a research program whose objective is embodied in the virtualization of the territorial heritage in general and, in particular, of the cultural heritage in order to restore it in network as a "common good" for citizens and visitors, also allowing local governments to internationalize the knowledge of that asset. It has been used an integrated approach in which play a key role not only local environment but also some advanced techniques that can ensure easy access to the network of services in line with the needs of residents and tourists, simultaneously allowing the same to interact and integrate information directly.